Membangun Sekolah yang Mendukung Setiap Peserta Didik untuk Sukses Tanpa Hambatan di Sekolah Menengah Atas Negeri 2 Palangka Raya - Arianto Wibowo; Christian Adi Saputra; Diah Puspita Ayu; Dwi Nurlita Febriyanti; Elmi Khoirina; Elva Febri Erenda; Kardalimah Kardalimah; Misnawati Misnawati; Olga Dona Retsi; Patrisia Cuesdeyeni; Linggua Sanjaya Usop (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This research aims to describe various obstacles faced by students at SMA Negeri 2 Palangka Raya in creating an educational environment that supports academic success and to describe strategies that can be implemented to overcome these learning barriers. The study employs a qualitative method through interviews, observations, and documentation. The results show that the obstacles faced by students at SMA Negeri 2 Palangka Raya include limited infrastructure, such as small classrooms and inadequate supporting facilities, as well as the socio-economic conditions of some students from less affluent families, making it difficult for them to meet basic educational needs. Lack of parental support also affects students' motivation and learning concentration. Additionally, limited access to the internet poses challenges in implementing digital-based learning methods. To address these obstacles, proposed strategies include improving infrastructure through collaboration with local government and private sectors, and optimizing the use of technology in learning. The implementation of these strategies are expected to create a conducive learning environment and support students' academic success.